Britain's exit from the European Union Its Causes and Repercussions on the Commercial Relations between the Two Parties (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This research aimed at presenting a historical presentation of the relations between Britain and the European Union and the repercussions of the British exit on the trade relations between the two parties during the period 2002-2021.The historical method relied upon to show the history of British relations, and the European Union and the reasons for Britain's exit from the Union, and the analysis of the tools and policies of the European Union and Britain towards trade exchange between them. The data on GDP, exports, imports and the trade balance were used to calculate the average annual increase, the average growth rate, and the degree of economic exposure.The most important conclusions of the research were that the most important of which are: the realization of both Britain and the European Union of the importance of continuing trade exchanges and increasing the movement of foreign trade in terms of exports and imports, which leads to an increase in the gross domestic product, and that there was no strong effect of Britain's exit from the European Union on the movement of foreign trade between them. Statistical analysis showed that the European economy is not exposed to the British economy, and the opposite is true. Among the most important recommendations reached by the research: Strengthening economic cooperation agreements between the two parties would contribute to increasing the gross domestic product and thus improving the per capita share of it.